A nonbehavioral theory of saving. Issue 4 (1st October 2016) - Nikiforos, Michalis
ABSTRACT: The article presents a demand-driven model, where the saving rate of households at the bottom of the income distribution becomes the endogenous variable that adjusts for full employment to be maintained over time. An increase in income inequality and the current account deficit and a consolidation of the government budget lead to a decrease in the saving rate of the household sector. Such a process is unsustainable because it leads to an increase in the debt-to-income ratio of the households and its maintenance depends on some kind of asset bubble. This framework allows us to better understand the factors that led to the Great Recession in the United States and the dilemma of the present and the future regarding a repeat of this unsustainable process or secular stagnation.